Społeczno-polityczny spór z końca lat 90. XX wieku na temat strefy ochronnej przy Muzeum Auschwitz–Birkenau w Oświęcimiu i jego konsekwencje - Klima, Zbigniew (Polityka i Społeczeństwo, 2021)
In the 1980's and 90's The Auschwitz-Birkenau Museum was witness to many disputes. The local community suddenly had to deal with international issues. Two decades of conflict have shown how important it is to build a reasonable boundary between the museum and the city. The problem with the "Zone of Silence" has grown into a problem that had to be solved by the Polish parliament. The consequences for the residents of Oświęcim were, however, considerable, and are felt to this day. A large part felt second-class citizens, and a drain of business from the city has been observed.